Satellite Communication Systems Design Principles - Richharia, M. (Macmillan Education UK, 1999)
This state-of-the art guide offers an in-depth treatment of the elements and components that comprise satellite communication systems. The book takes the reader step-by-step through the principles and methods of system design - all in easy-to-understand language avoiding long mathematical derivations